Gated communities in İstanbul - Kaya, Sibel Ekdemir. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This thesis aims to discuss the gated communities (GCs) in Istanbul and their effects on social division. The research was primarily based on in depth-interviews with residents, members of house owner association (HOA) in selected GCs and marketing professionals working on GC projects in Istanbul. The residents‘ reasons to move to the GCs, plans for future place of residence, their civic engagement experiences, relations with local authorities as well as the HOAs and perceptions about the people living in areas outside the gates were analyzed. Three GCs targeting different social classes were selected in order to observe whether there were differences in terms of motivations for moving to GCs, perceptions about GC life-style and about the outside world for the upper and middle classes. Conclusions showed that each group aimed to disintegrate itself from the lower social class as a sign of status and an exclusive life-style. Most residents described their reason to live in a GC as they were fearful of threats posed by the city which was inhabited by people of different backgrounds. However, such a fear of crime and demand for isolation increased as more security facilities were introduced in each GC. In other words, the more security controls and regulations were set, the more the residents felt insecure and anxious about the outside and thus demanded extra security measurements.|Keywords: gated communities, social division
Keywords: Gated communities -- Turkey.